Chemical Composition of the Essential Oil and Antimicrobial Activity of Scaligeria DC. Taxa and Implications for Taxonomy - Baldemir, Ayse; Demirci, Betul; Paksoy, Mehmet Yavuz; Ilgun, Selen; Kosar, Mberra; Baser, Kemal Husnu Can; Demirci, Fatih (Acg Publications, 2018)
Six different Scaligeria DC. taxa (Apiaceae) essential oils (EOs) obtained by hydrodistillation from herba with the flowers collected from different sites from Turkey. The oils were analyzed and characterized by gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS) simultaneously. A total of 133 different compounds were identified and relative qualitative and quantitative differences were observed among the evaluated samples. Analytical profiles of the Scaligeria EOs showed characteristic differences in terms of different main chemical constituents, between the two taxa S. lazica Boiss. and S. tripartita (Kalen.) Tamamsch; and S. napiformis (Sprengel) Grande, S. meifolia (Fenzl) Boiss., S. capillifolia Post, S. hermonis Post, S. glaucescens (DC.) Boiss. taxa, respectively. The main component germacrene D can be utilized as marker for the chemical discrimination of the Scaligeria genus. In addition, Scaligeria EOs were evaluated in vitro for their antimicrobial activity against pathogenic Gram positive (Staphylococcus aureus and Bacillus cereus), Gram negative (Pseudomonas aeruginosa) and yeast (Candida albicans, C. parapsilosis, and C. krusei) standard strains by using a micro-dilution assay. As a general result, the oils showed moderate inhibitory range when compared with standard antimicrobial agents.
Keywords: Scaligeria sp; chemo-taxonomy; essential oil; antimicrobial activity; Turkey